2016
DOI: 10.4236/ojce.2016.62014
|View full text |Cite
|
Sign up to set email alerts
|

The Types of Tunnels Maintenance in Umbrella Arch Method

Abstract: During tunneling in loose grounds, the ground deformation caused by drillings around the tunnel, leads to land subsidence and the adjacent tunnel which would affect tunnel structure and surrounding structures. In such situations it is necessary to improve the properties of the ground prior to drilling operations. In order to acquire tunnel face stability during excavation operations in areas with loose soil fault or areas with lack of adhesion, there are various methods such as split cross drilling, frame hold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Arch support methods and its techniques are very conventional and economical in tunnel excavation, and are being used to increase the excavation front sustainability, minimize the land subsidence, and prevent debris rocks falling into the tunnel [15]. The geological conditions and the stability of the rock mass in which a tunnel or cavern is to be excavated are probably the greatest sources of risk in a project involving underground construction.…”
Section: Arch Support Methodsmentioning
confidence: 99%
“…Arch support methods and its techniques are very conventional and economical in tunnel excavation, and are being used to increase the excavation front sustainability, minimize the land subsidence, and prevent debris rocks falling into the tunnel [15]. The geological conditions and the stability of the rock mass in which a tunnel or cavern is to be excavated are probably the greatest sources of risk in a project involving underground construction.…”
Section: Arch Support Methodsmentioning
confidence: 99%
“…Musivand and AskariZiyarati (2014) [10] investigate earth level settlement of tunnel digging by inserting harmonic loads with various frequencies and state that right and left side of settlement curve changes from sloppy to horizontal state by increase in frequency. [11] investigate the effect of tunnel maintenance on surface settlement. Rostami et al [11] (2016) evaluated the effect of tunnel maintenances on surface and concluded that an umbrella method had significant effect on surface.…”
Section: Introductionmentioning
confidence: 99%
“…[11] investigate the effect of tunnel maintenance on surface settlement. Rostami et al [11] (2016) evaluated the effect of tunnel maintenances on surface and concluded that an umbrella method had significant effect on surface. Rostami et al [12] (2016) evaluated effect of tunnels with different shapes on ground acceleration and conducted that the rectangular tunnel have a significant effect on ground responses.…”
Section: Introductionmentioning
confidence: 99%
“…They also noted that the earthquake acceleration domain has an important role in determining the acceleration of earth's surface earthquake reduction; so with increasing acceleration amplitude, earthquake acceleration decreases at ground level [17]. Rostami et al (2016) [18] studied the types of tunnel maintenances and its effect on surface acceleration. They studied on Sadr-Niayesh tunnel and stated that digging tunnel causes the increase in earthquake acceleration at ground level and at top of the tunnel, and that stresses around the tunnel become increased [19].…”
Section: Introductionmentioning
confidence: 99%